(untitled) (Revista Brasileira de Contabilidade e Gestão, 2019)
As a symbol, the brand becomes capable of impregnating itself with meanings to be conveyed to the consumer and of expressing the visibility of an internal discourse. The objective of this research is to identify the main methodological characteristics of Brazilian scientific studies of Marketing published on the “brand” theme for 11 years. We conclude that there was a lack of presentation of several of this information. This suggests the need to reinforce the teaching of research methods in academic environments, in order to make both authors and evaluators aware of the importance of credibility, transferability, trustworthiness, and confirmation of any scientific research.